Membrane electrode assembly for energy harvesting from salinity gradient by reverse electrodialysis - Kang, Byeongdong; Kim, Hyun Jung; Kim, Dong Kwon (Journal of Membrane Science, 2018)
In this study, the potential of the application of membrane electrode assembly (MEA) to energy harvesting from salinity gradient by reverse electrodialysis is experimentally investigated. The MEA, which consists of a cation exchange membrane and two porous silver/silver chloride electrodes, is developed. Power generation from the MEA located between sodium chloride solutions having various differences in concentration is measured. The highest power generation density achieved is 4.1 W m−2, which is greater than those reported in previous studies on conventional reverse electrodialysis cells.
Keywords: Cation exchange membranes; Membrane electrode assemblies; Porous silver; Reverse electrodialysis; Salinity gradients; Sodium chloride solution; Energy harvesting; Membrane electrode assembly; Reverse electrodialysis; Salinity gradient